Peer Support as Protective Factor Against Suicide Risk in Generation Z: Study in Indonesia - Renaldi, Shefi Rivan; Alfianto, Ahmad Guntur; Yuliyanik, Yuliyanik; Muanjan, Montira; Khan, Bachal (UNIVERSITAS ALIFAH PADANG, 2025)
Background: The mental health of Gen Z is a concern worldwide, of which suicide is one of the major causes of death. In collectivist societies such as Indonesia, the support of the peers may be a very important factor that protects the individual, however, there is still very little research evidence available to substantiate this.Objective: This study aimed to understand the association between peer support and suicide risk in Gen Z individuals from Malang City, Indonesia.Methods: A cross-sectional study was conducted on 207 Gen Z participants (mean age 21.37 years, 68.6% females) chosen through purposive sampling. Peer support was assessed by the Peer Social Support questionnaire (37 items, α=0.932), and suicide risk by the Revised Suicide Ideation Scale (10 items, α=0.941).Results: The prevalence of high suicidal ideation was 11.6%. There was a very strong correlation between peer support and suicide risk (χ2=112.847, p<0.001, Cramér's V=0.523). As many as 97.3% of those with high peer support had low levels of suicidal ideation, while 88.2% of those with low peer support showed high levels of suicidal ideation.Conclusion: There is a strong association between peer support and a decrease in the risk of suicide in Indonesian Gen Z which shows bigger effects than in the West. The results lead to the support of the implementation of culturally-appropriate peer-based interventions such as gatekeeper training and digital platforms.